COMPARISON OF HYDRODISECTION INJECTION BETWEEN TRIAMCINOLONE ACETONIDE VERSUS DEXAMETHASONE IN CARPAL TUNNEL SYNDROME - Widodo Mardi Santoso; Badrul Munir; Catur Ari Setianto; Ria Damayanti; Sheny Agma (Journal of Pain, Headache and Vertigo, 2021)
Background: Carpal tunnel syndrome (CTS) is the most common nontraumatic peripheral neuropathy, which is caused by suppression of the median nerve below the transverse carpi ligament. Local corticosteroid injection is considered the fastest and most effective method for improving symptoms that occur in CTS. There are several corticosteroid agents that can be used, but there are no objective standards that can explain the most ideal drugs. Objective: To compare the effectiveness of hydrodisection injection therapy of triamcinolone acetonide versus dexamethasone on carpal tunnel syndrome. Methods: This study involved 30 participants who were diagnosed with CTS and fulfilled the inclusion criteria and no exclusion criteria were obtained. Participants were divided into two treatment groups; the first group (n = 15) injected with Triamcinolone Acetonide (TCA) 10mg / 1ml and lidocaine 1% 1 ml and the second group (n = 15) injected with Dexamethasone 4mg / 0.8ml and lidocaine 1% 1 ml. The NRS, FSS, and SSS parameters were assessed before injection and 4 weeks after injection in each agent. Then compared these parameters at 4 weeks after injection compared to the TCA group with the dexamethasone group. Results: NRS score before and 4 weeks after TCA injection (sig 0.000; p <0.05), SSS (sig 0.001; p <0.05) and FSS (sig 0.020; p <0.05), and NRS score before and 4 weeks after dexamethasone injection (sig 0.001; p <0.05), SSS (sig 0,000; p <0.05) and FSS (sig 0,000; p <0.05). At 4 weeks after injection of TCA compared to dexamethasone there were no significant results on NRS (sig 0.237; p> 0.05) and FSS (sig 0.119; p> 0.05), while SSS values were significantly different (sig 0.027; p <0.05). Conclusion: Significant improvement in NRS, FSS and SSS score was obtained at 4 weeks after hydrodisection injection, both with TCA and dexamethasone. At 4 weeks after TCA injection compared to dexamethasone, there were no significant differences in NRS and FSS scores, whereas SSS score differed significantly. Both injection agents are equally effective in treating CTS, but dexamethasone produces a better improvement in SSS score.